Indicators of rheoencephalography in persons who have survived post-COVID syndrome (Environment & Health, 2025)
The purpose of this work is to study the state of cerebral hemodynamics in people who have had COVID-19, taking into account the severity of its course and auditory disorders.Materials and methods of the study. To study cerebral circulation, rheoencephalography was used in the frontomastoid and occipitomastoid leads, which reflect the state of cerebral circulation, respectively, in the carotid and vertebrobasilar systems. The examination was carried out using a computer rheograph of the company «DX-systems» (Ukraine).The probability of changes and differences between comparative values was assessed by the criterion of the reliability of the difference (t) according to the Student table.The 120 patients examined were divided into 2 groups according to the clinical course of the disease and the severity of sensory disorders: the 1st group included 74 patients who had moderate and less pronounced hearing, voice, and smell disorders after COVID-19, the 2-nd group included 46 patients who mainly had this infection in a more severe form and received persistent, progressive hearing disorders and changes in the nervous system. The control group consisted of 15 healthy normal individuals who did not have COVID-19.Results of the study and their discussion. Cerebral circulation disorders were found in all the examined patients, who had changes in cerebral vascular tone and difficulty in venous outflow, as well as a decrease in pulse blood filling in the vertebral-basilar system. This was evidenced by changes in α, dicrotic (DKI), diastolic (DSI) and rheographic (RI) indices of the REG curve in both cerebral blood supply systems.An increase in cerebral vascular tone in the carotid system occurred in 51.3% of patients in group 1 and 69.5% in group 2. In the vertebral-basilar system, these figures were 65.7% and 77.2% in groups 1 and 2, respectively. Venous outflow was obstructed in 64.3% of patients in group 1 and 75.8% in group 2 in the carotid system, 73.2% and 87.2% in the vertebral-basilar system, respectively.Conclusions. In patients of group 1, compared with the control group, changes in the quantitative indices of α, DKI and Ri were recorded, especially in the vertebral-basilar system. In patients of group 2, changes in almost all REG parameters were more pronounced, but this difference was significant only in the α index in the vertebral-basilar basin. The Ri value in both groups of patients indicates a decreased blood filling of the cerebral vessels in all patients with COVID-19, regardless of the degree of sensory system disorder. Moreover, the severity of such disorders is greater, the more significant the changes in the sensory systems in patients.
Keywords: diagnostics; treatment; olfactory analyzer; sensorineural hearing loss; auditory analyzer; central nervous system; cerebral hemodynamics; COVID-19; post- COVID